Effectiveness of Virtual Reality and Visual Feedback on Balance and Leg Function in Children with Cerebral Palsy - Arūnė Dūdaitė; Vilma Juodžbalienė (Lithuanian Sports University, 2019)
Research background. Virtual reality and visual feedback improve motor performance, motor function and balance, so we want to fnd if it aﬀects the function of legs and balance of children with spastic hemiplegia. Research aim was to establish if the use of virtual reality and visual feedback with traditional physiotherapy improve the function of legs and balance of children with cerebral palsy. Methods. Nine children with cerebral palsy participated in the research. Participants were randomly divided into two groups - virtual reality group (n = 6) and control (n = 3). Virtual reality group practised exergaming and stretching exercises for 10 weeks, twice a week. Control group practiced conventional physiotherapy and stretching exercises for 6 weeks, twice a week. We measured the range of motion of the lower limb, spasticity of the lower limb using Modifed Ashworth'o Scale, static, dynamic balance, trunk coordination using Trunk Impairment Scale at the start and the end of the research, and balance using Pediatric Balance Scale. Results. Virtual reality and visual feedback reduced the spasticity of the lower limb, improved balance and postural control for children with cerebral palsy, but it did not improve the range of motion of the lower limb of children with cerebral palsy. Conclusions. Virtual reality and visual feedback did not improve the range of motion of the lower limb of children with cerebral palsy. Virtual reality and visual feedback reduced spasticity of the lower limb, improved balance and postural control for children with cerebral palsy. Keywords. Cerebral palsy, virtual reality, visual feedback, postural control, muscle architecture.